Honey labeling: A qualitative analysis of compliance with regulations in packages sold in different cities in RJ and RS (Research, Society and Development, 2023)
The objective of this work was to assess compliance with current food labeling regulations on honey packaging sold in different establishments and municipalities in the states of RJ (Rio de Janeiro) and RS (Rio Grande do Sul) during the period from 2021 to 2022. To do this, 55 samples of honey packaging were acquired from eight cities in RJ and four in RS. Afterward, the samples were divided into three groups (RJ, RS, and Global), and then a table was organized with five categories (product origin, sanitary safety, customer service information, health precautions, and nutritional information), prepared in accordance with the current food labeling regulations. In this way, the information present on the labels was qualitatively evaluated. It was observed that within the analyzed groups, there were samples of honey packaging labels that did not conform to the standards specified by the current regulations, as well as packaging without labeling. This may be due to the existence of a series of laws, regulatory instructions, decrees, resolutions, which complement each other but can lead to misunderstandings on the part of honey producers. Furthermore, there is an inefficiency in the inspection of honey sales within these regions of the country. In this regard, it is concluded that there is non-compliance with honey labeling regulations, either due to labels with insufficient information or even the sale of unlabeled food, posing a risk to consumer health.